(untitled) (Journal of Bangladesh College of Physicians and Surgeons, 2011)
Cranio vertebral (CV) junction is one of the critical sites for surgery. It’s anatomy, physiological aspects and pathological involvement varies in a wide range of margins. Common problems are developmental anomalies, traumatic involvement, inflammatory, infective and neoplastic lesion. Management of these problems varies a lot from each other. Aim of the article is to overview the pathologies in this area and to study presentations, investigations, surgical procedures and results of these pathologies. We prospectively analyzed 32 cases of Cranio-vertebral (CV) region surgery in the Department of Neurosurgery Dhaka Medical College Hospital and Mitford Hospital, Dhaka, from 2000 to 2008. In our series, male and female ratio was 7.2:1. Pathologies were atlanto- axial dislocation (AAD), Chiari malformation type –I, schwannoma, meningioma, hydatid cyst and tuberculosis. Common clinical findings were- neck pain, quadriparesis, quadriplegia, hand atrophy, autonomic dysfunction and hypertension. Various types of surgical procedures were done in this series according to the pathology. Death was in 01 case, neurological deterioration seen in one case, 2 cases were neurologically stable and 28 cases (87.5%) improved neurologically where one was non useful improvement (Frankel grade-C). Complete pre operative radiological study is a very important adjunct for a successful surgical result. Proper evaluation of patients with selection of appropriate surgical procedures along with safe surgical techniques are the necessary things for successful surgery in this area. DOI: http://dx.doi.org/10.3329/jbcps.v29i2.7952 (J Bangladesh Coll Phys Surg 2011; 29: 78-84)